Reconstruction of the artificial knee joint using a reverse engineering approach based on computer-aided design. (17th February 2022) - Darmanto, D.; Novriansyah, R.; Ismail, R.; Jamari, J.; Anggoro, P. W.; Bayuseno, A. P.
Abstract: A greater flexion angle in total knee arthroplasty (TKA) is desirable for replacing the human knee joint damage of people living in the Middle East and Asian regions. This flexion angle is a significant clinical factor affecting the range of motion for patients. Therefore, this study aims to optimise the flexion angle in the design of the Artificial Knee Joint (AKJ) by tailoring the Posterior tibial slope (PTS) and thickness of the Posterior Femoral Condyle (PFC). The 3D CAD model of AKJ was obtained from the reverse engineering (RE) process. Furthermore, the physical model used as a standard implant produced by DePuy, Cruciate Substituting (CS)-Revision type. The obtained 3D models were subsequently converted into CAD for the reconstruction process. Reconstruction of the CAD Model with the customised PTS and FPC components provided the flexion angle in the range of 149.9°–166.7°, which is required for the motion suitable for Middle Eastern and Asian people. The results may be used as a reference standard for doctors in hospitals or industries to design AKJ with Asian ergonomics.